2006
DOI: 10.1016/j.destud.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Solution driven versus problem driven design: strategies and outcomes

Abstract: Data from protocol studies of nine experienced industrial designers, performing the same task, were analysed to develop an expertise model of the product design process. The protocol data and the expertise model were used to identify four different cognitive strategies employed by the designers: problem driven, solution driven, information driven, and knowledge driven design strategies. These strategies were then related to task outcomes such as solution quality and creativity, and to process aspects such as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(166 citation statements)
references
References 6 publications
9
151
0
6
Order By: Relevance
“…Evaluation entails the assessment of concepts against design requirements, constraints, and criteria [27] typically defined during problem analysis [47]. Authors were found to highlight the following as sub-activities involved in evaluation: comparing [4,41]; judging, on the basis of value [41,47], aesthetics [49], affect [4], or objective criteria [43,47,48]; and decision making with respect to which concept should be taken forward from a range of alternatives [43,47,48].…”
Section: Concept Generation and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation entails the assessment of concepts against design requirements, constraints, and criteria [27] typically defined during problem analysis [47]. Authors were found to highlight the following as sub-activities involved in evaluation: comparing [4,41]; judging, on the basis of value [41,47], aesthetics [49], affect [4], or objective criteria [43,47,48]; and decision making with respect to which concept should be taken forward from a range of alternatives [43,47,48].…”
Section: Concept Generation and Synthesismentioning
confidence: 99%
“…However, in certain studies, idea generation and synthesis are treated as separate activities [27,47]. In addition to synthesis, authors were found to highlight further sub-activities involved in concept generation, namely: memory retrieval [3,44]; association/analogical reasoning/case-based reasoning [3,21,25,45,48]; and the generation/transformation/ maintenance of internal representations [3,30,44].…”
Section: Concept Generation and Synthesismentioning
confidence: 99%
“…Models taking this view are often called solution-oriented (Wynn and Clarkson 2005). According to Kruger and Cross (2006), they are usually considered to be more realistic representations of the designer's thought process than models which suggest the top-down and abstract-to-concrete strategy exemplified in Fig. 3.…”
Section: Micro-level Abstract Modelsmentioning
confidence: 99%
“…Among the fundamental elements of the design process are the establishment of objectives and criteria synthesis, construction, testing and evaluation' (ABET 2012). To date, there has been a significant amount of research addressing the design education of engineering students, including (Atman et al, 1999, Atman and Turns 2001, Atman et al 2005, Bursic and Atman 1997, Christiaans and Dorst, 1992, Cross 2001, Ennis and Gyeszly 1991, Kruger and Cross 2006, Pahl 1999, Radcliffe and Lee 1989, Stauffer and Ullman 1988. However, there is limited research addressing the engineering design education of design students.…”
Section: Introductionmentioning
confidence: 99%